2013
DOI: 10.1111/add.12383
|View full text |Cite
|
Sign up to set email alerts
|

Balance—a pragmatic randomized controlled trial of an online intensive self‐help alcohol intervention

Abstract: Aims To compare a brief versus a brief plus intensive self-help version of 'Balance', a fully automated online alcohol intervention, on self-reported alcohol consumption. Design A pragmatic randomized controlled trial. Participants in both conditions received an online single session screening procedure including personalized normative feedback. The control group also received an online booklet about the effects of alcohol. The treatment group received the online multi-session follow-up program, Balance. Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 31 publications
0
58
0
Order By: Relevance
“…Among studies that reported racial/ethnic sample statistics, the samples were 72% White (SD = 20%), 34% Black (SD = 28%), and 13% Latino/a (SD = 10%). Countries other than the United States were as follows: Netherlands (Blankers et al., ; Riper et al., ); Norway (Brendryen et al., ); Canada (Cunningham, ); Ireland (Farren et al., ); Sweden (Gajecki et al., ); Australia (Kay‐Lambkin et al., , ); and United Kingdom (Wallace et al., ). Regarding sampling method, the majority of studies recruited participants from the community via online advertising ( k = 10), followed by within specialty clinics or medical facilitates ( k = 3), and 2 studies took place on college campuses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies that reported racial/ethnic sample statistics, the samples were 72% White (SD = 20%), 34% Black (SD = 28%), and 13% Latino/a (SD = 10%). Countries other than the United States were as follows: Netherlands (Blankers et al., ; Riper et al., ); Norway (Brendryen et al., ); Canada (Cunningham, ); Ireland (Farren et al., ); Sweden (Gajecki et al., ); Australia (Kay‐Lambkin et al., , ); and United Kingdom (Wallace et al., ). Regarding sampling method, the majority of studies recruited participants from the community via online advertising ( k = 10), followed by within specialty clinics or medical facilitates ( k = 3), and 2 studies took place on college campuses.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of CBT and motivational interviewing became increasingly common following the Combined Behavioral Intervention (CBI) approach (Combine Study Research Group, ) employed for AUD in the COMBINE Study (Anton et al., ). Other programs included in this meta‐analysis are “packaged” approaches that combine cognitive‐behavioral relapse prevention skills with personalized feedback, such as the Tertiary Health Research Intervention via Email ( THRIVE ; Leeman et al., ), or with acceptance and mindfulness exercises ( Balance ; Brendryen et al., ). Thus, the number of “pure” CBT technology‐based interventions, and therefore the evidence for their efficacy, is currently relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…When supplementary human support was used (for 7 trials that enrolled adults and 3 that enrolled students), it was typically limited, consisting only of technical support from a research assistant in more than one half of the cases (for 4 trials that enrolled adults and 3 that enrolled students). However, therapeutic support varied substantially, with some e-interventions supplemented by 1.5 to 6.5 hours of support (33)(34)(35)(36).…”
Section: E-intervention Characteristics and Supportmentioning
confidence: 99%
“…Related to this, a recent study on inhibition training for weight loss demonstrated that repeated food-related GNGT training via the internet led to significant weight loss that was maintained over four weeks [39]. Other interventions for problem drinking are also effective if delivered online in multiple sessions [40]. Overall, it appears that i) interventions targeting behaviour change are more effective if repeated in multiple sessions and ii) delivery of such interventions via the Internet can be efficient, cost-effective and efficacious [41, 42].…”
Section: Introductionmentioning
confidence: 99%